18F-Fluorodeoxysorbitol PET for noninvasive detection of invasive mold infections: preclinical and first-in-human studies - Carlos E. Ruiz-Gonzalez; Oscar J. Nino-Meza; Medha Singh; Yuderleys Masias-Leon; Amy Kronenberg; Madelynn Shambles; Xueyi Chen; Elizabeth W. Tucker; Martin A. Lodge; Laurence S. Carroll; Kenneth R. Cooke; Olivia S. Kates; et al. (Nature Communications)
Abstract Invasive mold infections are a major cause of mortality in immunosuppressed and cancer patients. Diagnosis is challenging, requiring invasive procedures or reliance on fungal biomarkers with limited sensitivity and an inability to detect non-Aspergillus molds. Here, we perform whole-body 18F-fluorodeoxysorbitol (18F-FDS) positron emission tomography (PET) in nine prospectively enrolled patients with high-suspicion of invasive mold infections (eventually confirmed using culture or molecular assays, n = 4) or other pathologies (n = 5) with localization of 18F-FDS PET signal to infection sites as the primary outcome (NCT05611892). 18F-FDS PET (120 or 180 min after injection), rapidly detects and localizes invasive pulmonary and cerebral infections due to Aspergillus, non-Aspergillus (galactomannan-negative), or azole-resistant molds, and differentiates them from sterile inflammation or cancer. Moreover, 18F-FDS selectively and rapidly accumulates intracellularly in a range of clinically relevant molds, including azole-resistant molds, via a saturable process. In animals, 18F-FDS PET is able to detect and localize pulmonary and cerebral aspergillosis, as well as rhinosinusal infections due to Aspergillus, Rhizopus, and Mucor, confirming the clinical data. 18F-FDS can be easily synthesized from 18F-fluorodeoxyglucose (18F-FDG), which is widely available, and represents a promising, noninvasive diagnostic tool for detecting, localizing and monitoring of invasive mold infections throughout the body.